PENGENDALIAN KOMISARIS DAN DIREKSI PADA KOMPONEN ISLAMIC SOCIAL RESPONSIBILITY (ISR) DAN PENGELOLAAN ZAKAT DALAM MENINGKATKAN PROSES BISNIS BANK SYARIAH - Frastuti, Melia; Habibie, Azwansyah; Effendi, Erfan; Yustriawan, Dian (School of Accountancy, University of Agung Podomoro, 2021)
The purpose of this study is to see the need for Islamic banks in reducing usury in the community, making Islamic banks demanded to be active and productive both on the financial side as learning in business processes in order to grow and develop to serve customers and society. This study upgrades the role of directors and commissioners of Islamic commercial banks in Indonesia on the component of Islamic Social Responsibility (ISR) and zakat management to improve the business processes of Islamic banks in the future, using summantive evaluation methods, namely research whose purpose is to see the effectiveness of a program. The results of this study indicate that it is necessary to upgrade the role of commissioners to be better, while the role of directors is generally strong. The control of commissioners and directors as Islamic Financial Management in Islamic banks must be upgraded so that Islamic banks are not abandoned by customers and society by themselves.